Alterations of Cytochrome P450s and UDP-Glucuronosyltransferases in Brain Under Diseases and Their Clinical Significances - Sheng, Yun; Yang, Hanyu; Wu, Tong; Zhu, Liang; Liu, Li; Liu, Xiaodong (Frontiers in Pharmacology, 2021)
Cytochrome P450s (CYPs) and UDP-glucuronosyltransferases (UGTs) are both greatly important metabolic enzymes in various tissues, including brain. Although expressions of brain CYPs and UGTs and their contributions to drug disposition are much less than liver, both CYPs and UGTs also mediate metabolism of endogenous substances including dopamine and serotonin as well as some drugs such as morphine in brain, demonstrating their important roles in maintenance of brain homeostasis or pharmacological activity of drugs. Some diseases such as epilepsy, Parkinson’s disease and Alzheimer’s disease are often associated with the alterations of CYPs and UGTs in brain, which may be involved in processes of these diseases via disturbing metabolism of endogenous substances or resisting drugs. This article reviewed the alterations of CYPs and UGTs in brain, the effects on endogenous substances and drugs and their clinical significances. Understanding the roles of CYPs and UGTs in brain provides some new strategies for the treatment of central nervous system diseases.